Short Communication: Assessment of reclamation success of former limestone quarries in Tuban, Indonesia, based on soil arthropod diversity and soil organic carbon content - DWI OKTAFITRIA; KUNTUM FEBRIYANTININGRUM; NURUL JADID; NIA NURFITRIA; FAHMI RAHMADANI; ALFIAN AMRULLAH; DEWI HIDAYATI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Oktafitria D, Febriyantiningrum K, Jadid N, Nurfitria N, Rahmadani F, Amrullah A, Hidayati D. 2019. Assessment of reclamation success of former limestone quarries in Tuban, Indonesia, based on soil arthropod diversity and soil organic carbon content. Biodiversitas 20: 1743-1747. The reclamation for sustainable ecosystem in mined land, including revegetation, is an obligatory program stipulated by the Indonesian government. This study evaluated the ecological improvement of revegetated land at the reclamation sub-areas (RSAs) of former limestone quarries in Tuban, East Java, Indonesia. The RSAs were coded as RSA 2010, RSA 2014, and RSA 2016 which represented the initial year of revegetation as well as the reclamation soil-material, namely the rejected soil-products, topsoil, and spoils, respectively. Soil insects were collected from ten sampling plots at each RSA using pitfall traps. The data of arthropods were analyzed to describe the community structure by determining the Shannon Diversity Index (H’), Simpson’s index (D), Sorensen's similarity and Shannon evenness index (E). The soil organic carbon (SOC) content from the soil composites was analyzed according to the Walkley and Black method. The results showed that SOC value at RSA 2010 (1.851±0.38%) was higher than that at SRA 2014 (1.694±0.29%) and SRA 2016 (0.947±0.10%). There were 18 families found from eight orders of soil insects (Coleoptera, Diplura, Diptera, Entognatha, Hemiptera, Hymenoptera, Neuroptera, and Orthoptera) and one order from terrestrial crustacea i.e., Isopoda, family Tylidae. The ecological indices of RSA 2014 (H’=1.15; D=0.47; E=0.61) and RSA 2016 (H’=1,19; D=0.47; E=0.57) were higher than those of RSA 2010 (H’=0,61; D=0.71; E=0.43). The Pearson analysis indicated moderate negative correlation (r=0.55) between soil arthropod diversity index and SOC. The diversity of soil arthropods at reclaimed area indicated that the reclamation was successful. Based on the study, we recommend that reclamation is done using mine spoil or topsoil rather than rejected soil products.